A sala de aula invertida como técnica alternativa de ensino : um enfoque no desenvolvimento da autonomia do aprendiz de inglês como L2/LE - Ofugi, Mariana Santana (2016)
This study aims at investigating in what ways the work with the flipped classroom (a procedure through which students should study specific parts of the course content at home, through videos, for example, before they are discussed in the classroom) can help English as a foreign language students become more autonomous in their learning process. It also aims at analyzing the perceptions of the students and the teacher-researcher after they have worked under the flipped classroom model. This qualitative case study research was carried out at the Language Center at the Federal University of Goiás. 14 learners, mostly university students, and the teacher-researcher participated in the research. The data collection instruments were a questionnaire applied to students before they started working with the flipped classroom, an interview with the learners which was conducted by the end of the term, three video recorded classes and the field notes created by the teacher-researcher. The results showed that the learners displayed various signs of developing autonomy and a high level of cooperation throughout the classes. Their perceptions regarding the work with the flipped classroom were, for the most part, positive: many of them said they benefitted from being able to access the class content beforehand, and other learners stated that they preferred the flipped classes, since they were more dynamic. Some of the negative perceptions regard the fact that oftentimes they would forget to watch the videos, since they were not used to working under this technique. The teacher-researcher also benefitted from the work with the flipped classroom, mostly because it proved to be challenging and stimulating. In the final thoughts section, we discuss aspects such as the necessity of the teacher carefully performing an evaluation of their class before starting the work with the flipped classroom. This should be done in order to ensure all students have access to the materials and that they know what is expected from them in this way of having classes, which is probably new to them.